1992
DOI: 10.3109/00365529209000117
|View full text |Cite
|
Sign up to set email alerts
|

Interdigestive Gastroduodenal Motility and Cycling of Putative Regulatory Hormones in Severe Obesity

Abstract: The aim of the present study was to evaluate interdigestive gastrointestinal motility and its coordination with plasma concentrations of motilin and pancreatic polypeptide (PP) in 14 patients with severe obesity and in 10 control subjects with normal body weight. Motor activity of the stomach, duodenum, and proximal jejunum was recorded by using an eight-lumen catheter. Blood samples were drawn for determination of interdigestive motilin and PP plasma concentrations. We observed no difference in total duration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
1
1

Year Published

1996
1996
2016
2016

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 24 publications
2
22
1
1
Order By: Relevance
“…Although plasma levels were overall higher in the obese patients the fluctuation of motilin plasma levels was diminished (19). Our findings of elevated motilin levels are in agreement with two other studies reporting significantly higher motilin plasma levels in obesity (15,40,59). Hunger measurements showed lower hunger scores during phase III in the obese compared with the healthy controls, which is probably due to the shift in origin from gastric to duodenal, despite the higher motilin plasma levels (19).…”
Section: The Role Of the MMC And Motilin In Food Intake Disorderssupporting
confidence: 82%
See 1 more Smart Citation
“…Although plasma levels were overall higher in the obese patients the fluctuation of motilin plasma levels was diminished (19). Our findings of elevated motilin levels are in agreement with two other studies reporting significantly higher motilin plasma levels in obesity (15,40,59). Hunger measurements showed lower hunger scores during phase III in the obese compared with the healthy controls, which is probably due to the shift in origin from gastric to duodenal, despite the higher motilin plasma levels (19).…”
Section: The Role Of the MMC And Motilin In Food Intake Disorderssupporting
confidence: 82%
“…In 1992 Pieramico et al (40) reported that obese patients had significantly fewer phase III contractions that started in the stomach compared with healthy controls. This change in origin was associated with significantly lower motilin plasma levels in the obese patients compared with the lean controls.…”
Section: The Role Of the MMC And Motilin In Food Intake Disordersmentioning
confidence: 99%
“…Circulating hormones have been implicated in adult constipation 8 and in severe obesity. 9 Therefore, reasons for this association could be multifactorial, including diet, activity level, or hormonal influences, and require additional studies.…”
Section: Discussionmentioning
confidence: 99%
“…Basel U 0012-2823/97/0582-0115S12.00/0 E-Mail karger^'kargcr.ch F ax+ 41 61 306 12 34 http:// www. karger, ch nied by decreased plasma motilin concentrations at all phases of the migrating motor complex as compared with controls, but by a normal secretion of pancreatic polypep tide [6]. Whether these findings contribute to the etiology of obesity is not clear [6].…”
Section: Introductionmentioning
confidence: 99%